Measurement of Thermal Expansion Coefficient on Electric Cable Using X-Ray Digital Microradiography - Yessi Affriyenni; Gede Bayu Suparta; Galandaru Swalaganata (Proceeding of the Electrical Engineering Computer Science and Informatics, 2018)
Electric cable is a medium to conduct electrical energy. Expansion and contraction caused by thermal changes may result in an aging effect on the cable. This paper presents the way to observe the expansion in electrical cable due to thermal changes using the x-ray microradiography. The observed electric cables were NYA, NYAF, and NYM, each with cross-sectional areas of 1.5 mm 2 and 2.5 mm 2 . The temperature was monitored using a DS18B20 sensor compiled into a microcontroller. In order to process and analyze the cables images, an ImageJ software was used. The image differences were compared based on the value of the digital image correlation. The physical analysis was carried out based on Adrian's FWHM and calculated using the regression method. The accurate structural dimension measurement using x-ray digital microradiography is about 50 μm/pixel. The average relative error measured was less than 3%.